The numerical analysis of human body movement during falls and spine response in contact sports - Gzik, M.; Tejszerska, D.; Wolanski, W.; Potkowa, P. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
This paper presents modelling process and numerical analysis of human body behaviour during accidents in contact sports and its consequences for human cervical and lumbar spine. The researches contain creation of model which enables human body motion analysis in a situation corresponding to real falls with simultaneous analysis of internal physiological phenomena in human spine. The model of falling man was created using Working Model 2D program and used to numerical analysis of human motion in frontal plane under dynamical loading corresponding to falls in sport.